Размерный эффект при смачивании упругодеформируемой подложки - Бородин, А.А.; Гладких, Н.Т.; Дукаров, С.В. (ХНУ имени В. Н. Каразина, 1998)
Рассматривается уменьшение краевого угла смачивания, обусловленное деформации подложки и размерными зависимостями удельных энергий поверхностей раздела жидкость-пар и жидкость-подложка, которые объясняются увеличением вклада граничного слоя по сравнению с объемом капли при уменьшении ее размера. На примере системы Au/C показано, что вклад деформации подложки в изменение краевого угла является незначительным. . . . . . . . . . . . . . . . . . . . Розглядається зменшення крайового кута змочування, обумовлене деформацією підкладки і розмірними залежностями енергій поверхнь розділу рідина-пара та рідина- підкладка, які пояснюються збільшенням вкладу перехідного шару порівняно з об'ємом краплі при зменшенні її розміру. На прикладі системи Au/C показано, що вклад деформації підкладки у зміну крайового кута є незначним. . . . . . . . . . . . . . . . . . . . A wetting angle decrease due both to elastic deformation of a substrate and size dependences of specific energies of liquid vapour and liquid substrate interfaces is considered. These dependences are attributed to the increase of the contribution introduced by the surface layer as compared to the drop volume one, the drop size being decreased. For Au/C system tne substrate deformation is shown to make a small contribution to the wetting angle variation.
Size effect in wetting an elastically deformable substrate
Keywords: Thin films; surface energy; Wetting; size effect; Research Subject Categories::NATURAL SCIENCES::Physics::Condensed matter physics::Surfaces and interfaces